Analyzing Fast-ions Trajectories in a Nuclear Fusion Reactor through Its Poincaré-Island Size and Ripple Resonance - Kurniawan, Anggi; Tsutsui, Hiroaki (Indonesian Journal of Computing, Engineering and Design, 2021)
Fast-ions confinement is a prominent subject in developing nuclear fusion reactors due to its importance in sustaining the burning plasma and keeping energy production. However, confining them has proven to be difficult until now, and one of the reasons is that the inherent discrete magnetic field produces a magnetic ripple. A better understanding of fast-ions transport using appropriate numerical calculation tools needs to be developed to overcome such a challenge in the engineering aspect. This study revisited data collection of fast ion transport simulated under the ripple presence in a nuclear fusion device. The ion trajectories were followed using two orbit-following equation schemes, and the ripple-resonance island size in the Poincaré section was compared. The result showed that the island size obtained by each scheme was different when the particle resonates with a stronger ripple field and, proportionally, the diffusion coefficients are different. The physical meaning and consequence behind this discovery were discussed in this paper.